Evolution of the Contact-Fatigue Defects Caused Rail Failure Rate - E. A. Shur; A. I. Borts; A. V. Sukhov; A. Yu. Abdurashitov; L. V. Bazanova; K. L. Zagranichek (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
There is discussed current situation and problems of rail damageability in operation. It has been indicated that contact-fatigue defects coded as 10, 11, 17, 21 in the standing catalogue of rail defects represent the main type of rail defects responsible for over 50 % of the total number of cases of rail withdrawal from the track. There was studied character of emergence and development of the contact-fatigue rail defects at present day. Thus it was shown that surface layer destruction of the rail head metal affected by cyclic inelastic deformation (and not non-metallic impurities of steel or presence of brittle-fractured non-metallic inclusions, such as aluminum silicates or other multiple oxides) was mainly responsible for their emergence. Specification of main destruction stages of the rail head metal and investigation of various stage processes was carried out at the JSC VNIIZhT Experimental Loop through the example of the I Class rails T1 (GOST R 51685 - 2000). It was found that at various destruction stages of the rail head metal there take place: formation of the cold-worked layer with fibre-strained pearlite microstructure, reduced by a quarter instantaneous strength and four-times reduced percentage extension; flaw development and formation of small pittings with their further development into chippings with depth up to 4.0 mm; emergence of longitudinal flaws up to 6 - 10 mm in depth with their further turning and developing of lateral fatigue flaws. For investigated rails there was obtained passed tonnage dependence of the chipping depth. It is proposed to determine frequency and regimes of in-track preventive rail grinding not only on the basis of irregularities’ development rate but also on the basis of surface flaw/chipping deepening law in terms of increase in the passed tonnage under specified operating conditions. Also there is noted the necessity of special-purpose flaw-detection equipment creation intended to determine the depth of surface flaws.